Istri Nusyûz dalam Pandangan Ulama Pedesaan - Ahmad Nabil Atoillah; Desi Nurjanah; Fidya Rahma Insani (Istinbath | Jurnal Penelitian Hukum Islam, 2021)
Marriage as a legal act between husband and wife is not only meaningful to realize worship to Him, but at the same time creates a consequence of civil law between the two. However, because the purpose of marriage is so noble, that is to foster a happy, eternal, eternal family based on the One God Almighty, it is necessary to regulate the rights and obligations of each husband and wife. One of these obligations is a matter of providing a living. The obligation to provide a living according to the ulama is due to three things: the existence of a marital relationship, the existence of a kin relationship and the existence of a property relationship. In domestic life there is not always harmony in reality, humans cannot always follow the teachings recommended by the Qur'an. Al-Quran recommends that if there is a husband and wife dispute, then settle it properly by way of deliberation. However, even this settlement sometimes lacks justice for each party, so that sometimes wives do nusyuz actions.